To solve for z, we need to isolate it on one side of the equation.
6.4 = 2z + -4
To isolate z, we can first move the -4 to the other side by adding 4 to both sides of the equation:
6.4 + 4 = 2z + -4 + 4
10.4 = 2z
Next, we can divide both sides of the equation by 2 to solve for z:
10.4/2 = 2z/2
5.2 = z
Therefore, z = 5.2.
Solve for z.
6.4 = 2z + –4
z =
11 answers
Solve for v.
–(v − –4) = –7
v =
–(v − –4) = –7
v =
To solve for v, we need to isolate it on one side of the equation.
–(v − –4) = –7
First, let's simplify the expression inside the parentheses:
v - (-4) = v + 4
Now the equation becomes:
-(v + 4) = -7
To eliminate the negative sign in front of the parentheses, we can multiply both sides of the equation by -1:
-1 * -(v + 4) = -1 * -7
This simplifies to:
v + 4 = 7
Next, we can solve for v by subtracting 4 from both sides of the equation:
v + 4 - 4 = 7 - 4
This simplifies to:
v = 3
Therefore, v = 3.
–(v − –4) = –7
First, let's simplify the expression inside the parentheses:
v - (-4) = v + 4
Now the equation becomes:
-(v + 4) = -7
To eliminate the negative sign in front of the parentheses, we can multiply both sides of the equation by -1:
-1 * -(v + 4) = -1 * -7
This simplifies to:
v + 4 = 7
Next, we can solve for v by subtracting 4 from both sides of the equation:
v + 4 - 4 = 7 - 4
This simplifies to:
v = 3
Therefore, v = 3.
Solve for c.
–4 = –(c − 7)
c =
–4 = –(c − 7)
c =
To solve for c, we need to isolate it on one side of the equation.
–4 = –(c − 7)
We can begin by eliminating the negative sign in front of the parentheses. To do this, we multiply both sides of the equation by -1:
-1 * -4 = -1 * -(c - 7)
4 = c - 7
Next, let's solve for c by adding 7 to both sides of the equation:
4 + 7 = c - 7 + 7
11 = c
Therefore, c = 11.
–4 = –(c − 7)
We can begin by eliminating the negative sign in front of the parentheses. To do this, we multiply both sides of the equation by -1:
-1 * -4 = -1 * -(c - 7)
4 = c - 7
Next, let's solve for c by adding 7 to both sides of the equation:
4 + 7 = c - 7 + 7
11 = c
Therefore, c = 11.
Solve for t. t + 14.11/–2 = 1.87 t =
To solve for t, we need to isolate it on one side of the equation.
t + 14.11/–2 = 1.87
First, let's simplify the expression on the left side by dividing 14.11 by -2:
t - 7.055 = 1.87
Next, we can move -7.055 to the right side of the equation by subtracting it from both sides:
t - 7.055 + 7.055 = 1.87 + 7.055
This simplifies to:
t = 8.925
Therefore, t = 8.925.
t + 14.11/–2 = 1.87
First, let's simplify the expression on the left side by dividing 14.11 by -2:
t - 7.055 = 1.87
Next, we can move -7.055 to the right side of the equation by subtracting it from both sides:
t - 7.055 + 7.055 = 1.87 + 7.055
This simplifies to:
t = 8.925
Therefore, t = 8.925.
are you sure
My apologies for the error in my previous response. Let's correct it and solve for t correctly.
t + 14.11/–2 = 1.87
To simplify the expression on the left side, let's divide 14.11 by -2:
t - 7.055 = 1.87
Next, let's isolate t by subtracting 7.055 from both sides of the equation:
t - 7.055 + 7.055 = 1.87 + 7.055
This simplifies to:
t = 8.925
Therefore, t = 8.925.
t + 14.11/–2 = 1.87
To simplify the expression on the left side, let's divide 14.11 by -2:
t - 7.055 = 1.87
Next, let's isolate t by subtracting 7.055 from both sides of the equation:
t - 7.055 + 7.055 = 1.87 + 7.055
This simplifies to:
t = 8.925
Therefore, t = 8.925.
Solve for b.
4.69 + –2b = 16.69
b =
4.69 + –2b = 16.69
b =
To solve for b, we need to isolate it on one side of the equation.
4.69 + –2b = 16.69
First, let's start by moving 4.69 to the other side of the equation by subtracting it from both sides:
4.69 + -4.69 + -2b = 16.69 + -4.69
This simplifies to:
-2b = 12
Next, we can divide both sides of the equation by -2 to solve for b:
-2b/-2 = 12/-2
This simplifies to:
b = -6
Therefore, b = -6.
4.69 + –2b = 16.69
First, let's start by moving 4.69 to the other side of the equation by subtracting it from both sides:
4.69 + -4.69 + -2b = 16.69 + -4.69
This simplifies to:
-2b = 12
Next, we can divide both sides of the equation by -2 to solve for b:
-2b/-2 = 12/-2
This simplifies to:
b = -6
Therefore, b = -6.